Colombia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper describes economic developments in Colombia during the 1990s. Economic activity slowed in 1991 as financial policies were tightened to curb inflation. However, activity rebounded strongly to an average of 5 percent a year in 1992-94, buoyed by the trade and financial liberalization, the discovery of substantial new oil fields, relaxation of credit policies, and higher coffee export prices in 1994. Substantial growth was recorded in investment, transport, construction, and service activities, and the unemployment rate fell from 10.5 percent in 1990 to 7.9 percent by end-1994, notwithstanding a moderate increase in labor force participation.